Self-Governance: Internationalization Management of Distinctive Higher Education Towards The World Class University - Djalal Fuadi; Harsono Harsono; Muhammad Fahmi Johan Syah; Agus Susilo; Samsudin Suhaili; Budi Wahyono (Universitas Muhammadiyah Surakarta, 2021)
The purpose of this study is to describe the management of the internationalization process of higher education in the form of self-governance, strategic plans (vision, mission, and objectives), institutional management, curriculum and learning processes, and quality assurance. The research applied a qualitative approach. The scope of the research is limited to the policy/ legal framework for managing the internationalization of higher education at three Islamic universities in Yogyakarta, comprising the State Islamic University of Sunan Kalijaga Yogyakarta, the Islamic University of Indonesia, and the Muhammadiyah University of Yogyakarta. The data collection was conducted through the techniques of; (1) participant observation, (2) in-depth interviews, and (3) document study. The data analyses used are (1) on-site data analysis and (2) cross-site data analysis. The results of the study showed that the process of self-governance towards higher education institutions with international competitiveness was divided into several stages, namely: determination of the vision, mission, and objectives; development of learning and curriculum which are equivalent to foreign universities; recruitment of foreign students and lecturers; and quality assurance that prioritizes technology, ISO standards, orientation changes, and overall quality assurance. The self-governance accommodates the rapid change and unpredictable education situation due to many factors such as technology, social changes, society health issue, and disruption advanced education in pandemic era. In the context of tertiary management, distinctive competences in the future need to be adapted to distinctive management courtesy. For example, the internalization of speech acts according to local culture is one of the characteristics that can improve the sustainability of higher education.